(untitled) - Leroy, Stephen F (New York, 2001)
'This is an excellent introduction to the exciting field of financial economics, rigorous yet filled with economic intuition, and with a refreshing emphasis on equilibrium that is reminiscent of Debreu's elegant and pithy monograph.' Andrew Lo, Massachusetts Institute of Technology
Kinh tế học tài chính và ngân hàng
Keywords: Investments,Finance,Economics,Kinh tế; Mathematical models,Mathematical models,Mathematical models,Mô hình toán học